Assessment of Capsular Contracture Based on Morphological Change of Breast Implant Using Computed Tomography - Oh, Won Seok; Lee, Seung Hoon; Lee, Jae Woo; Seo, Jung Yeol; Kim, Choong Rak; Nam, Su Bong (Archives of Plastic Surgery, 2025)
Capsular contracture is a common complication following implant-based breast reconstruction. Current assessment methods, primarily relying on the subjective Baker grading system, lack objectivity and quantitative data, which hinders large-scale studies and the development of treatment guidelines. To solve these problems, we conducted a study using computed tomography (CT) scans to quantitatively evaluate morphological changes in breast implants associated with capsular contracture.We enrolled 94 patients who underwent breast reconstruction using implants and underwent periodic chest CT scans. We categorized them into two groups: Baker grade I or II (n = 72) and Baker grade III or IV (n = 22). We analyzed the CT scans to assess changes in the implant base and projection.In the Baker grade III or IV groups, it was confirmed that the ratio of projection to base increased after capsular contracture compared with before contracture. On the other hand, there was no significant change in the ratio of projection to base in the Baker grade I or II groups.This study highlights the potential of CT scans as a reproducible method for evaluating capsular contracture. The ratio of projection to base could serve as a new quantitative index alongside the Baker grades for clinical assessment, treatment planning, and research on capsular contracture. When comparing the ratio of projection to base before and after capsular contracture, if the ratio of projection to base increases by more than 1.233 times, it can be considered Baker grade III or IV.
Keywords: breast implant; capsular contracture; Computed tomography